A THINK-ALOUD PROTOCOLS AS A COGNITIVE STRATEGY TO INCREASE STUDENTS’ WRITING NARRATIVE SKILL AT EFL CLASSROOM - Purwo Trapsilo (Premise Journal, 2016)
The purpose of this study was twofold: its first aim was to know whether any differences of think-aloud potocols to develop writing narrative skill; second, to know whether which one is more effective to develop students’ writing narrative skill by using think-aloud protocols and traditional method. Students randomly assigned to an experimental and a control group. Treatment had three stages. In Stage 1, students were asked to write about a topic. In Stage 2, students in the experimental group studied a model essay about that writing task and they had think-aloud protocol about those aspects of language that they noticed in the model essays. However in the control group, students studied model essays for themselves and they did not have think-aloud part. In Stage 3, students were asked to rewrite the writing task. The students in the experimental group showed that they got higher score in writing narrative by using think-aloud protocols than the control group. Furthermore, in the post test, experimental group outperformed the control group. The findings of the study suggest that thinking-aloud could be a good strategy for improving writing narrative performance.